Identification of the Elderly's Nutritional Status in Institutions - Sumandar; Yelfira Sari (Journal of Global Research in Public Health, 2022)
The nutritional problems of the elderly are directly related to their physical condition, so it affects their strength in carrying out daily routines.The aim of the research was to evaluate the nutritional status of the elderly.. The research method is quantitative with descriptive. A Mini Nutritional Assessment (MNA) questionnaire was used to collect data. The number of sample were 51 elderly with purposive sampling technique. The results showed that 15.7% were malnourished, 58.8% were at risk of malnutrition, 25.5% were normal. It is suggested to policymakers that nurses pay special attention by constantly monitoring nutritional status,developing nutrition programs, and involving external factors.